Perlukah Mempertahankan Keunggulan Kompetitif oleh UMKM? (Studi Kasus UMKM Semarang) - Jaluanto Sunu Punjul Tyoso; Caecilia Sri Haryanti (Universitas Proklamasi 45 Yogyakarta, 2020)
This study is to find out and analyze how Small and Medium Enterprises (SMEs) maintain their competitive advantage so that they can survive or even develop from the time they have been established until now. For achieving the goal, this research used a qualitative approach. It is intended to explore the managerial actions of SMEs in maintaining a competitive advantage. The results of the study show that a competitive advantage can be owned through SOAR (Strength, Opportunity, Aspiration, Result). The strength consists of skilled workers, loyal customers, products according to consumer tastes, product and production process innovations, and adequate business land. The opportunity consists of the quality of the production process, broadening the marketing reach from domestic to foreign, and managerial capabilities supported by International Standard for Organization (ISO) 9000-2000 quality management systems that have an impact on increasing consumer confidence. But not many SMEs have been able to implement a quality management system. The aspiration is to work with several souvenir sellers around them and with export brokers. The result is expected to increase sales by participating in online exhibitions and promotions and improving the production process so that the products tend to be near to zero defect rate.